The Role of Digital Leadership in Enhancing Data-Driven Instruction and Curriculum Design in Higher Education - Rokimin; Rika Handayani; Sofwan Manaf; Dudun Ubaedullah; Farah Diba (Jurnal Pendidikan Indonesia, 2026)
The integration of digital leadership in the higher education ecosystem is a fundamental prerequisite for strengthening data-driven instructional decision-making. This study aims to explore the optimization of the role of digital leadership in integrating artificial intelligence (AI) and data-driven strategies to improve pedagogical effectiveness and learning outcomes. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews, focus group discussions, participatory observation, and documentation analysis of academic leaders, educators, and educational technology specialists as key informants. Data were analyzed using thematic analysis techniques through a process of data reduction, categorization, and iterative conclusion drawing. The results show that effective digital leadership requires leaders to act as mediators between the technological and pedagogical dimensions, going beyond mere technical mastery. The success of integration depends on a systematic, step-by-step approach and the continuous strengthening of educators' digital competencies, despite the challenges of the digital divide and institutional resistance. This study concludes that digital transformation requires a holistic approach that includes strengthening infrastructure, continuous professional development, and equitable accessibility strategies.